The effect of atorvastatin on the erythrocyte plasma membrane and C-reactive protein in menopausal women with metabolic syndrome - Franiak-Pietryga, Ida; Balcerak, Magdalena; Sikora, Joanna; Duchnowicz, Piotr; Koter-Michalak, Maria; Stetkiewicz, Tomasz; Broncel, Marlena (Menopause Review/Przegląd Menopauzalny, 2009)
The aim of the study was to estimate the effect of atorvastatin (10 mg/d) on serum lipids, C-reactive protein and erythrocyte structure membrane (membrane cholesterol, the activity of Na+/K+-ATPase) in menopausal women with metabolic syndrome (MS). Material and methods: The study comprised 20 menopausal women (mean age 55 ±3,69). Waist circumference ł 80 cm, triglycerides (TG) level >150 mg/dl (1,7 mmol/l), cholesterol HDL level < 50 mg/dl (1,3 mmol/l), systolic blood pressure (SBP) ł 130 mm Hg and/or diastolic blood pressure (DBP) ł 85 mm Hg were inclusion criteria for patients with MS. Control group consisted of 18 healthy women (mean age 55 ±6,48). Before and after 4 and 12 weeks of treatment the following parameters were determined: serum lipids (total cholesterol – TC, cholesterol LDL, cholesterol HDL, TG – by means enzymatic method), hsCRP (immunoenzymatic method), membrane cholesterol in erythrocytes (method of Ilcy) and Na+/K+-ATPase activity (method of Bartosz et al.). Results: It was noticed significantly higher concentrations of hsCRP and membrane cholesterol in erythrocytes of menopausal women with MS. Atorvastatin caused a significant decrease, after 4 weeks therapy, in serum TC, cholesterol LDL, TG, hsCRP and membrane cholesterol (by 47%) in comparison with the initial values before active therapy. The activity of Na+/K+-ATPase has significantly changed after 12 weeks of therapy (increase by 29%). The mean values of TC, cholesterol LDL-C and membrane cholesterol after 12 weeks of therapy were similar to the control group. Conclusions: Three-months treatment of atorvastatin was enough efficient to compensate disorders in erythrocyte membrane structure of menopausal women with MS.